Pemanfaatan Kain Perca sebagai APE Pillow Doll untuk Pembelajaran Anak Usia Dini - Aliva Rosdiana; Hayu Dian Yulistianti; Azzah Nor Laila (Universitas Islam Nahdlatul Ulama Jepara, 2018)
Some people have not realized that waste can be used as multifunctional goods. This is become a problem complained by householder in the neighborhood at Kuwasen, Jepara. Therefore the use of patchwork can be a solution to overcome waste processing problem. Team of community service invited the group of PKK at Kuwasen as partners to carry out activities of illumination and motivation, training, and evaluation. Based on community service activities, team and partners succeeded in making APE Pillow Doll, as well as the socialization of its use as a home based education media. The outcome of APE Pillow Doll can be applied as a medium for learning English and Hija'iyyah for early childhood, both in the home and formal school.